Simulação por dinâmica molecular de óxidos alcalino-terrosos - Oliveira, Rita de Cássia Mota Teixeira de (Universidade Federal de São Carlos, 2006)
The main subject of this work is to simulate structural and dynamical properties of MeO type alkaline-earth oxides, where Me is an element of the family 2 (Me = Ca, Sr and Ba). The use of the Molecular Dynamics method (MD) was implemented in isobaric-isoenthalpic ensemble (N, P, H), in which the volume is a dynamical variable, in order to study the eﬀect of the pressure and the temperature on such materials. The interaction potential between atoms consists of a pair potential, known as Vashishta- Rahman potential, characterized by terms that represent the steric repulsion, the Coulomb interactions due to charge transfer, the induced charge-dipole interaction due to the large electronic polarizability of the ions, and the last is the van der Waals dipole-dipole interaction. The simulations had been carried out for the three systems composed of 1728 atoms, 864 Me− type atoms and 864 oxygen O . The study of the temperature dependence is carried through the heating of such systems with a rate 4.59 K/ps and, after to reach the solid-liquid phase transistion, each system was submitted to cooling with the same rate that it was heated. Through the trajectories in the phase space it was possible to calculate the density of vibrational states, the pair distribution function, from which it was possible to determine the behavior of the Debye-Waller factor, and the temperature and pressure frequency coeﬃcients for each material. The eﬀect of the hydrostatic pressure on the systems was studied through the implementation of the statical and dynamical calculations. In the first study is possi- xi ble to determine the energetic sequency of the allotropic forms, the cohesivy energies, bulk modules, lattice parameters for each phase of each material. The static pressures of structural phase transistion, between the B1(N aCl) and B2(CsCl) phases, for calcium (CaO), strontium (SrO) and barium (BaO) oxides, were 71.5 GP a, 34 GP a and 105 GP a, respectively. Through the dynamic application of hydrostatic pressure to the systems, the structural phase transformations were observed from B1(N aCl) to B2(CsCl) phases, around 100 GP a, 90 GP a and 220 GP a for calcium (CaO), strontium (SrO) and barium (BaO) oxides, respectively. The confirmation of the structural phase transformations was given by the changes in the coordination number from 6 to 8 (MeO), in the bond angles (O − Me − O) −type from 90◦ and 180◦, B1(N aCl) phase, to 70◦, 109◦ and 180◦ (O − Me − O), which are the characteristic angles of the B2(CsCl) phase, and by the change in the pair distribution functions from the characteristic peaks of the B1(N aCl) phase to the characteristic peaks of the B2(CsCl) phase. A comparison with the experimental results in literature is made in order to validate our results.
Keywords: Mecânica estatística; Simulação; Dinâmica molecular; Óxidos; CIENCIAS EXATAS E DA TERRA::FISICA